Waterproofing process of swimming pool / Norhafizah Rahmat - Rahmat, Norhafizah (Universiti Teknologi MARA, Perak, 2017)
Practical Training refers to work experience that is relevant to professional development prior to graduation. One of the requirements for the students of Diploma in Building Surveying to complete the program is the students must complete at least 14 weeks of Practical Training. It started on 1st December 2016 until 31th March 2017. During the four months of practical training at Zikay Group Sdn. Bhd, Kampung Baru, Kuala Lumpur, have learned how theory and practical can be combined together in useful ways and how remarkable and enjoyable practical training could be. While deadlines and skills are highly demanded, creativity is not limited and true innovation occurs throughout my practical training at Kembang Serantau Sdn Bhd. As a result, more knowledge can gained and learned new things and most importantly had experienced the real working environment all by myself. In term of relationship, feel was lucky enough to work with a group of enthusiastic and communicative people, who for whatever reason willing to share their knowledge and experience of what they are doing. Besides, the atmosphere at Kembang Serantau is unique and hope that it will stays that way. The experience gained has been an eye opening to me and thoroughly recommend other students to do their industrial training at here to enable them to have the same experience as at Kembang Serantau Sdn Bhd.